Certainty in Election Law in 2019 Concurrent Elections Through Regulation of the General Election Commission of the Republic of Indonesia - Herawati, Ratna; Sukma, Novira Maharani; Hananto, Untung Dwi (Law Research Review Quarterly, 2018)
Legal certainty and the integrity of the process and results of elections are a sign of the process of holding democratic elections. One form of election law certainty in Indonesia is accommodated in Law Number 7 of 2017 concerning General Elections. In addition, in Law Number 7 of 2017 concerning General Elections it gives authority to the General Election Commission (KPU) to form KPU Regulations so that the process of organizing elections is more democratic. On the other hand, often the emergence of KPU Regulations causes the process of the stages of election management to change so that raises the question whether KPU Regulations guarantee the certainty of election law, especially in the 2019 Concurrent Election. This study uses a normative juridical method with conceptual and statutory approaches. The results of this study are that the KPU Regulations established in the process of holding the 2019 Concurrent Election have largely provided legal certainty, although there are several KPU Regulations that are not in line with the Law above. Basically, the KPU regulations when viewed from the side of benefits and justice provide legal certainty.